A unique style of computer-assisted assessment - Thelwall , Mike (Research in Learning Technology)
The Computer-Based Assessment project at the University of Wolverhampton has produced a number of tests built around a common framework. There are three main tests that are used by about 800 students per year, and they replace written tests. There are also two diagnostic tests that are not part of any formal assessment but are used by about 400 students per year. We have produced numerous special versions of these tests for short courses, different teaching techniques, and one for a Broadnet Online training module (Broadnet, n.d.). The tests are all written with 80,000 permutations built in to allow them to be made available for students to use and practise on at all times without compromising security. In fact, there are no serious security concerns because of the random factors, and so the same tests are used every year without the need to be hidden or rewritten. Similar advantages have been found on other projects using random factors; see for example Thoennessen and Harrison (1996). DOI:10.1080/0968776980060205